Kepemimpinan Transformasional Kepala Sekolah dalam Meningkatkan Motivasi Kerja Guru di Sekolah Dasar Negeri 172 Bengkulu Utara - Sihandi Sihandi; Rambat Rambat; Connie Connie (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research aims to describe the transformational leadership of principals in improving the motivation of teachers' work at public elementary school 172 Bengkulu Utara which includes: idealized influence, providing inspirational motivation to teachers , encouraging intellectual stimulation in the implementation of the duties of teachers, providingin dividualized consideration to teachers at school. The method used was descriptive qualitative with interview, observation, and documentation techniques. Data analysis was done using Miles and Huberman interactive model. The results of the study show (1) The principal demonstrates ideal influence through exemplary attitudes, integrity, and ethical practices that build a healthy organizational culture and increase teacher loyalty and performance; (2) Through inspirational motivation, the principal strengthens teacher involvement by conveying a clear vision, providing emotional support, and forming a participatory and adaptive work climate; (3) Principal sencourage intellectual stimulation by creating an innovative and collaborative environment, facilitating professional development, and appreciating teachers' creativity; (4) With individualized attention, principals support the development of teachers' potential through personal communication, training, mentoring, and empathic approaches that strengthen the positive work climate and quality of learning.